Design, Fabrication, and Modulation of THz Bandpass Metamaterials. Issue 11 (14th October 2019) - Wang, Qinghua; Gao, Bingtao; Raglione, Michaella; Wang, Huixin; Li, Baojia; Toor, Fatima; Arnold, Mark A.; Ding, Hongtao
Abstract: Development of terahertz (THz) sources, detectors, and optical components has been an active area of research across the globe. The interest in THz optoelectronics is driven by the various applications they have enabled, such as ultrawide‐band communication systems, air‐ and space‐borne astronomy, atmospheric monitoring, small‐scale radar, airport security scanners, ultrafast nanodevices, and biomedical imaging and sensing. Here, the aim is to provide a comprehensive review of THz bandpass metamaterials focusing on several areas. First, the design fundamentals and geometrical patterns of THz bandpass metamaterials are summarized. Second, fabrication methods of THz bandpass metamaterials are reviewed, including typical micro‐ and nanofabrication techniques and laser micromachining techniques. More importantly, different engineering methods are reviewed for tuning and modulation of the THz transmission resonance for these metamaterials. Both passive and active modulation methods are included in this discussion; the passive method involves changes in the geometrical pattern of the filter material, and the active method performs in situ modulation of properties by applying an external physical field. Finally, the potential applications and prospects for future research of THz bandpass metamaterials are discussed. Abstract : The interest in terahertz (THz) optoelectronics is driven by various applications such as ultrawide‐band communication systems, atmospheric monitoring, airport security scanners, and biomedical imaging and sensing. A comprehensive overview of THz bandpass metamaterials is given, with focus on the design strategies, fabrication techniques, modulation methods for transmission resonance, and applications.